Novel ectopic expression of zona pellucida 3 glycoprotein in lung cancer promotes tumor growth - Pulawska-Moon, Kamila; Ponikwicka-Tyszko, Donata; Lebiedzinska, Weronika; Pilaszewicz-Puza, Agata; Bernaczyk, Piotr; Koda, Mariusz; Lupu, Oana; Milewska, Gabriela; Huang, Chen-Che Jeff; Zheng, Huifei; Schiele, Phillip; Na, Il-Kang; et al. (John Wiley & Sons, 2025)
Zona pellucida 3 (ZP3) expression is classically found in the ZP-layer of the oocytes, lately shown in ovarian and prostate cancer. A successful ZP3 ovarian cancer immunotherapy in transgenic mice suggested its use as an attractive therapeutic target. The biological role of ZP3 in cancer growth and progression is still unknown. We found that ~88% of the analyzed adenocarcinoma, squamous and small cell lung carcinomas to express ZP3. Knockout of ZP3 in a ZP3-expressing lung adenocarcinoma cell line, significantly decreased cell viability, proliferation, and migration rates in vitro. Zona pellucida 3 knock out (ZP3-KO) cell tumors inoculated in vivo in immunodeficient non-obese diabetic, severe combined immunodeficient mice showed significant inhibition of tumor growth and mitigation of the malignant phenotype. RNA sequencing revealed the deregulation of cell migration/adhesion signaling pathways in ZP3-KO cells. This novel functional relevance of ZP3 in lung cancer emphasized the suitability of ZP3 as a target in cancer immunotherapy and as a potential cancer biomarker.